Identification of Lactobacillus spp. Isolated from Different Phases During the Production of a South African Fortified Wine - Stratiotis, A.L.; Dicks, L.M.T. (South African Journal of Enology and Viticulture, 2017)
Fortified wines contain a high level of unfermented sugars and are prone to spoilage by alcohol-tolerant lactic acid bacteria. A total of 62 strains were isolated from various production stages of one of the more popular fortified wines produced in South Africa. The strains were identified by using numerical analysis of total soluble cell protein patterns and 16S rRNA sequence analyses. The species most frequently isolated were Lactobacillus vermiforme (24 strains) and Lactobacillus casei subsp. casei (32 strains).  Twenty-four of the strains of L. vermiforme, three strains of Lactobacillus buchneri, one strain of Lactobacillus plantarum and two strains of L. casei subsp. casei were isolated from spoiled fortified wine which contained 22% (vol/vol) ethanol. The majority of strains of L. casei subsp. casei (25 of the 32) and two strains of Lactobacillus zeae were isolated from wine before submerged fermentation. Five strains of L. casei subsp. casei were isolated from wine undergoing submerged fermentation, with an alcohol content of 11.92% (vol/vol). No strain was isolated from unbottled wine which underwent the complete fermentation process and with an alcohol content of 17.20% (vol/vol). Three distinct phenotypic groups of L. vermiforme were identified at r ≥ 0. 70, separate from Lactobacillus brevis,' L. buchneri and Lactobacillus hilgardii. Three phenotypic clusters have been identified for L. casei subsp. casei. This is the first report of the presence of L. vermiforme, L. zeae, L. casei subsp. casei and L. plantarum in fortified wines.